2014
DOI: 10.1038/ejhg.2014.189
|View full text |Cite
|
Sign up to set email alerts
|

Gene by stress genome-wide interaction analysis and path analysis identify EBF1 as a cardiovascular and metabolic risk gene

Abstract: We performed gene-environment interaction genome-wide association analysis (G × E GWAS) to identify SNPs whose effects on metabolic traits are modified by chronic psychosocial stress in the Multi-Ethnic Study of Atherosclerosis (MESA). In Whites, the G × E GWAS for hip circumference identified five SNPs within the Early B-cell Factor 1 (EBF1) gene, all of which were in strong linkage disequilibrium. The gene-by-stress interaction (SNP × STRESS) term P-values were genome-wide significant (Ps = 7.14E − 09 to 2.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 35 publications
11
54
1
Order By: Relevance
“…We validated the computed scores of chronic psychosocial stress by observing moderately strong and significant correlations with the self‐rated chronic psychosocial stress in the Multi‐Ethnic Study of Atherosclerosis Cohort (Rho = 0.23, P < 0.0001) and with the measures of depressive symptoms in five datasets (Rho = 0.15–0.42, P s = 0.005 to <0.0001) and by comparing the distributions of the self‐rated and computed measures. Finally, we demonstrate the utility of this computed chronic psychosocial stress variable by providing three additional replications of our previous finding of gene‐by‐stress interaction with central obesity traits [Singh et al., ].…”
supporting
confidence: 77%
See 1 more Smart Citation
“…We validated the computed scores of chronic psychosocial stress by observing moderately strong and significant correlations with the self‐rated chronic psychosocial stress in the Multi‐Ethnic Study of Atherosclerosis Cohort (Rho = 0.23, P < 0.0001) and with the measures of depressive symptoms in five datasets (Rho = 0.15–0.42, P s = 0.005 to <0.0001) and by comparing the distributions of the self‐rated and computed measures. Finally, we demonstrate the utility of this computed chronic psychosocial stress variable by providing three additional replications of our previous finding of gene‐by‐stress interaction with central obesity traits [Singh et al., ].…”
supporting
confidence: 77%
“…We applied the foregoing method of computing a chronic psychosocial stress measure and performing subsequent analysis on the following datasets, using the available relevant psychosocial and socioeconomic data, genotypic data of EBF1 SNP rs4704963 (or LD SNP rs17056278) genotyped in genome‐wide array or as individually genotyped candidate SNPs, and phenotypic data for central obesity trait (hip circumference or BMI). MESA : The original GWAS study [Singh et al., ] used the MESA dataset because it had a self‐rated chronic psychosocial stress (chronic burden) variable [Bild et al., , Shivpuri et al., ]. In the current work, we used this dataset to compare the self‐rated chronic psychosocial stress measure with computed chronic psychosocial stress scores.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction reached genome-wide significance among the subset of 2460 Whites in the Multi-Ethnic Study of Atherosclerosis (MESA) but was not significant among Chinese Americans, Blacks or Hispanics. This study reported that the impact of risk allele carriage in EBF1 on hip circumference was greater among participants with a greater chronic stress burden [161]. The authors also replicated the interaction between psychosocial stress and three of the original five SNPs (rs17056278 C>G, rs17056298 C>G and rs17056318 T>C) in EBF1 in the Framingham Offspring cohort [161].…”
Section: Obesity-predisposing Gene Variants Interact With Psychosociamentioning
confidence: 74%
“…This study reported that the impact of risk allele carriage in EBF1 on hip circumference was greater among participants with a greater chronic stress burden [161]. The authors also replicated the interaction between psychosocial stress and three of the original five SNPs (rs17056278 C>G, rs17056298 C>G and rs17056318 T>C) in EBF1 in the Framingham Offspring cohort [161]. A subsequent analysis by the same research group replicated the EBF1 × psychosocial stress interaction on obesity (waist circumference or BMI) in the Family Heart Study Whites and at trend level in the Duke Caregiver study [162].…”
Section: Obesity-predisposing Gene Variants Interact With Psychosociamentioning
confidence: 90%
See 1 more Smart Citation